Overview in Abnormal Read Cell Lipidomic Profiling for Human Chronic Disorder Diagnosis - Dackouo, Blaise; Arama, Dominique Patomo; Dembele, Ousmane; Toure, Hamadoun Abba; Mariko, Madani; Koumare, Benoît Yaranga; Kanoute, Gaoussou (European Journal of Applied Sciences, 2024)
Red blood cell lipidomics has merged as new way to explore chronic disease biomarkers. The aim of this review to explore ethics sample collection and treatment for lipidomics purpose. Samples used to perform lipidomics is also addressed herein. As a result, remarkable efforts are made is the field.